Letter from Thomas H. Garrett to Margaret M. Booth - Garrett, Thomas H. (1888)
Thomas H. Garret requests Margaret M. Booth née Cardeza forward several chemical texts kept in her late husband's office for inclusion in his library.
Keywords: Booth, James Curtis, 1810-1888; Garrett, Thomas H.; Martinez Cardeza, Margaret